Plan de negocios para la puesta en marcha de una empresa de reciclaje y tratamiento de cartón en la ciudad de Santa Marta (2021)
In order to apply all the knowledge acquired throughout the training process in the Business Administration career and in the different topics addressed in the different areas of application, the business plan is made to verify the viability of the start-up of a cardboard recycling and treatment company in the city of Santa Marta. The main functions of the company will be the purchase, treatment and pertinent disposal of recyclable material, which due to its poor treatment cause damage to society and the environment. The raw material, the object of development of the company, will be obtained directly from the Samarian society, especially the places most frequented by residents and tourists, after this they will be taken to cycles of productive reintegration and finally offered to companies in charge of the processing and essential use of these materials. Finally, this business plan generates great expectations in terms of its profitability and positive impact from the technical and functional aspects, responding to social and environmental needs for the formalization of good practices in the recycling of reusable products, this proposal will be focused on the treatment of cardboard.